Synthesis and Characterization of Hydroxyapatite via Microwave‐Assisted Method - Md. Kawsar; Md. Sahadat Hossain; Tasnimul Quader Tazim; Newaz Mohammed Bahadur; Samina Ahmed (International Journal of Ceramic Engineering & Science)
ABSTRACT This study used the microwave synthesis method to manufacture nanocrystalline hydroxyapatite (HAp), a calcium and phosphate group mineral with a hexagonal lattice structure. Calcium hydroxide and diammonium hydrogen phosphate were used as precursors for calcium and phosphorus. The crystalline structure of the resultant HAp was identified by X‐ray diffraction (XRD). Various XRD models, including the Scherrer method, Williamson–Hall (W‐H) method, Halder–Wagner (H‐W) method, size–strain plot (SSP) method, modified Scherrer (MS) method, linear straight line (LSL) method, and the Sahadat–Scherrer method, were employed to estimate crystallite parameters such as size and strain. W‐H analysis is utilized to determine data about crystallite size and lattice strain with the help of models such as UDM, USDM, and UDEDM to estimate crystallite dimensions. The estimated crystallite size of HAp using this method ranges between 1 and 100 nm. The FTIR analysis verified the incorporation of PO43− and OH− groups in the synthesized HAp.